Increasing levels of grain supplementation for intensive-early stocked steers: two-year summary - Cochran, R.C.; Brandt, Robert T., Jr.; Vanzant, E.S.; Clary, E.M.; Owensby, Clenton E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
During the first 2 yr of a 4-yr experiment, increasing the level of grain sorghum supplementation (from 2 to 4 Ibid) for steers managed within an intensive-early stocking program tended to increase average daily gain in direct proportion to supplement level (2.3 (no supplement) to 2.5 and 2.7 lb/d, respectively). During both years, the amount of grass remaining in the pastures after the cattle were removed (July 15) and at the end of the growing season (October 1) was greater when cattle were supplemented with 4 lb of grain sorghum. Level of supplementation for grazing steers did not influence subsequent feedlot performance.
Keywords: Beef; Intensive-early stocking; Supplementation; Grain sorghum; Stockers